Pengaruh Quality Service Dan Promotion Terhadap Buying Decision Pada Toyota Auto 2000 Sungkono Di Surabaya - Alfiah Alfiah; Handik Purwantoro; Muhammad Aris Hidayatulloh (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
The study aims to determine the effect of quality service and promotion on buying decisions at Toyota Auto 2000 Sungkono in Surabaya. The quantitative research method uses a questionnaire instrument with a Likert scale and the sampling technique uses the accidental sampling method. Data analysis techniques with validity tests, reliability tests, classical assumption tests and multiple linear regression analysis tests. Based on the results of the study, it is known that the validity test is declared valid and the reliability test is declared reliable. Quality service has a significant effect on buying decisions and promotion also has a significant effect on buying decisions. Quality service and promotion have a significant effect on buying decisions.